Linear optimization in the harmonization of regional dishes and wines from the São Francisco Valley (Research, Society and Development, 2022)
The junction between wine and food is called harmonization and this practice provides the combination of flavors, favoring the contemplation of foods and drinks with greater balance, without the flavors overlapping, thus ensuring to appreciate the main characteristics of both. The present work aims to apply linear optimization in the harmonization of regional dishes and wines from the Submédio Vale do São Francisco. A survey of eight wines and ten dishes was carried out, seeking to evaluate the relationships between some foods and wines in the region. Grades from 1 to 5 were assigned to the harmonies, classifying them as 'no harmony', 'refreshment', 'neutral', 'good harmonization' and 'synergistic correspondence', assuming the situation in which each dish and each wine could only be paired once, without repetition. For this, a mathematical optimization tool was used to obtain an optimal result for a situation with more than a million different possibilities of choice. The results for the problem of the best choice between wine and food obey the existing rules of harmonization, making it more efficient and showing that the mathematical application has the possibility of solving a real problem.